2017
DOI: 10.1007/s11187-017-9945-8
|View full text |Cite
|
Sign up to set email alerts
|

The “why” of international entrepreneurship: uncovering entrepreneurs’ personal values

Abstract: Previous studies investigating the "why" of entrepreneurial internationalization have focused on firm-level motivations, overlooking the relationships between firm-level and individual-level motivations and why entrepreneurs differ in the goals they intend to achieve. We investigate the role of personal values as desirable end states that motivate international entrepreneurship by functioning as superordinate cognitive structures that underlie the practical internationalization goals set by entrepreneurs. By a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 136 publications
2
49
0
Order By: Relevance
“…To do this, I excluded those linkages that were not significant across the sample because they appeared only in a few respondents' ladders by calculating a cut-off level above which elements and linkages are represented (Appendix , Table A3). Applying a cut-off of three linkages, consistent with other studies (e.g., Bagozzi & Dabholkar, 1994;Bolzani & Foo, 2017;Pieters et al, 1995), I graphically represented 67% of total linkages. 9 The hierarchical value map for this study is shown in Figure 2.…”
Section: Means-end Chains About Financial Remittancessupporting
confidence: 82%
“…To do this, I excluded those linkages that were not significant across the sample because they appeared only in a few respondents' ladders by calculating a cut-off level above which elements and linkages are represented (Appendix , Table A3). Applying a cut-off of three linkages, consistent with other studies (e.g., Bagozzi & Dabholkar, 1994;Bolzani & Foo, 2017;Pieters et al, 1995), I graphically represented 67% of total linkages. 9 The hierarchical value map for this study is shown in Figure 2.…”
Section: Means-end Chains About Financial Remittancessupporting
confidence: 82%
“…We advance theory on the role of cross-cultural experiences and intercultural dynamics at the individual-level in entrepreneurship research (e.g., Bolzani and Foo, 2017 ; Clark et al., 2018 ; Jones and Casulli, 2014 ; Morgan et al., 2018 ; Williams and Gregoire, 2015 ). We specifically shed light on the influential role of cross-cultural experience in itself and the formation of intentions to engage in entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a rather large unexplained variance in our results. Future investigations may want to combine SDT with other theoretical frameworks such as theory of planned behavior (Ajzen, ), goal setting theory (e.g., Locke and Latham, ), personal values (e.g., Bolzani and Foo, ), or theory of job design (Hackman and Oldham, ) to better understand citizen participation in open government platforms. Second, this analysis indicates that types of motivation are related to varying levels of platform activity.…”
Section: Discussionmentioning
confidence: 99%